(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
L’art. 9 della Convenzione E.D.U. secondo la giurisprudenza recente della Corte E.D.U. (2018-2023) ABSTRACT: The right to religious freedom is constantly changing, following the contemporary treatment of the religious phenomenon within the public sphere of the states. This finding is also evident in the ECHR’s jurisprudence, which since the Kokkinakis case seems to have made great progress in the development of the more specific manifestations of religious freedom, such as religious autonomy. In this context, an attempt is made to draw conclusions regarding the right of religious freedom under the related ECHR’s case law. SOMMARIO: 1. Introduction - 2. Freedom of Assembly and Association - 3. Respect for family and private life - 4. Religious freedom in prison - 5. Religious Minorities: the example of Jehovah’s Witnesses - 6. The example of Greece - 7. Conclusion.